Strategic Development of VOEs in Natural Resource-Based Sectors: Insights from Agriculture and Tourism - Sari, Nelly Purnama; Rachmina, Dwi; Kolopaking, Lala M. (Agro Bali : Agricultural Journal, 2025)
Badan Usaha Milik Desa (BUMDes) or Village-Owned Enterprises (VOEs) play an essential role in developing the rural economy. Unfortunately, there are numerous hurdles that VOEs must overcome, therefore many do not perform optimally. This study aims to examine how internal and external factors affect VOE performance in the agricultural and tourism sectors to boost rural economic development. Alternative solutions are then presented to improve VOE's performance. The study employs two samples: one VOE focuses on agriculture and the other on tourism. Observation, in-depth interviews, and a literature review were used to collect data, which was then evaluated using A'SWOT (AHP and SWOT). The findings demonstrate that both industries face infrastructure restrictions, market competitiveness, and poor branding. For agricultural VOEs, incorporating digital marketing to increase market reach, fortifying branding, and growing distribution networks are important tactics. Meanwhile, tourism VOEs should prioritize branding to boost destination appeal and infrastructure development to improve accessibility. Strengthening local branding through a compelling narrative and utilizing technology-driven marketing are critical for competitiveness. By implementing these strategies, VOEs can improve sustainability, attract a wider market, and support rural economic growth. Integrating branding, digital marketing, and infrastructure development ensures adaptability in an increasingly competitive landscape.